Pengembangan Model Assessment for Learning dalam Pembelajaran Matematika di Kelas VII SMP - Ruslan; Nurwati Djam‘an; Sahid (Universitas Negeri Makassar, 2023)
This study aims to develop an Assessment for Learning (AFL) instrument on a quadrilateral for student at grade VII junior high school students and an assessment for learning model. The type of research used is Research and Development (R&D). The subjects in the study were two expert validators and 34 grade VII students at SMP Tunas Harapan Malaka Makassar. The objects in this study are validity, difficulty, and discriminating power, as well as the AfL learning model. The results showed that: (1) a test instrument consisting of 5 essay questions met the validity aspect; (2) in terms of student learning outcomes, meeting the indicators of completeness of student learning outcomes classically; (3) in terms of the level of difficulty, 5 points (100%) with the difficulty category of medium questions; (4) in terms of discriminating power, there are five questions (100%) that meet the criteria for good questions so they do not need to be revised; (5) in terms of AfL strategy, including Phase I: (Initial Activities) Conveying learning objectives to students; Phase II: (Core Activities) Helping students to know and understand the standards they want to achieve; Phase III: Guiding working and study groups; Phase IV: Engage students in assessment including self-assessment; Phase V Provide feedback; Phase VI: Giving awards. The results showed that the instruments developed were valid, and the Assessment for Learning (AfL) learning model on the quadrilateral material developed in the research has the potential to foster critical attitudes and curiosity. AfL learning, positions students in an equal position in assessment, enabling the student to conduct self-introspection that impacts improving students' mathematical abilities.